Related services needed by the multi handicap children and their families and availability from the perspective of parents and teachers - Bander Al Otaibi (Journal of Educational Sciences, 2012)
This study aimed to identify the nature of the support services needed by children with multiple disabilities and their families, and the adequacy of services provided to them from the viewpoint of parents and teachers. To achieve the objective of the study the researchers applied a list of supported services, which included two parts; the supported services needed to children, and supported services and assist to the family of the children. The study sample contained of (106) of parents (83), and teachers (23) of children enrolled in the multiple disabilities centers and special education programs in regular schools in Riyadh. The results of the study revealed: 1. Parents and teachers agreed that children with multiple disabilities and their families in need to all services included in the list of supported services, although there were a variation between the two groups toward the type of services more needed. 2. There were significant differences between parents and teachers in regard to the adequacy of services provided to children and their families. Parents indicated that they either do not receive services at all, or what they receive is not enough. They rarely indicated that services they received are enough. On the other hand, teachers indicated that the services they received are either adequate or not enough.They rarely indicated that they do not receive services.